Pengaruh Gaya Kepemimpinan Transformasional, Keseimbangan Kehidupan Kerja (WLB), dan Motivasi Intrinsik Terhadap Kinerja Karyawan di PT Hanil Indonesia - Taufik Adnan; Muhammad Syihabuddin (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
This study aims to analyze the influence of transformational leadership style, work-life balance, and intrinsic motivation on employee performance at PT Hanil Indonesia. The research employed a quantitative approach using multiple linear regression analysis methods. Research data were collected through questionnaires distributed to employees as research respondents. The collected data were then analyzed to determine the influence of each independent variable on the dependent variable, both simultaneously and partially.The results of the study indicate that simultaneously transformational leadership style, work-life balance, and intrinsic motivation have an influence on employee performance with a contribution of 56.1%, while the remaining percentage is influenced by other factors outside this study. Partially, transformational leadership style has a positive and significant effect on employee performance. Intrinsic motivation also has a positive and significant effect on employee performance. Meanwhile, work-life balance does not have a significant effect on employee performance.This study concludes that inspirational leadership and intrinsic motivation are the main factors in improving and maintaining employee performance amid the pressures of the national textile industry.